DISEMANIASI HASIL PENELITIAN POTENSI DAN MANFAAT WISATA BUDAYA SUKU ANAK DALAM AIR HITAM BUKIT DUA BELAS PROVINSI JAMBI - Sadzali, Asyhadi Mufsi (Bhakti: Jurnal Pengabdian Masyarakat, 2025)
The expansion of oil palm plantations around Bukit Dua Belas National Park in Jambi over the past few decades has not only contributed to climate change but has also significantly impacted the socio-cultural and economic life of the indigenous Suku Anak Dalam community, who have inhabited the forest as their settlement for hundreds of years. Jambi, with its vast tropical forest potential, is not only rich in biodiversity but also holds important cultural value, particularly from the Suku Anak Dalam Air Hitam community. In recent decades, this community has faced agrarian, social, and economic conflicts as a result of palm oil plantation development, which has increasingly narrowed their living and hunting areas in the Bukit Dua Belas region. This shrinking space has led to socio-economic and cultural disruptions, including members of the Suku Anak Dalam descending to urban areas to beg for a living. In an effort to mitigate this social and cultural degradation, a cultural-economic approach has been proposed, introducing the concept of special interest cultural tourism based on local wisdom. The dissemination of this initiative was conducted directly in the field using a cultural communication approach, involving discussions with traditional leaders of the Suku Anak Dalam. As a result of this dissemination on the potential and economic benefits of cultural tourism, several mutual understandings and agreements were reached. These include a shared commitment to develop cultural potential into special interest tourism, the willingness of the Suku Anak Dalam Air Hitam to welcome tourists under the condition that visitors respect and adhere to local customs and traditions, and an agreement that tourists who violate customary rules must pay a fine in the form of a piece of cloth. Additionally, the local government has committed to further study and formulate regulations that will support and protect this initiative.